Conservation status of North Pacific right whales - Brownell, Robert L.; Clapham, Phillip J.; Miyashita, Tomio; Kasuya, Toshio (J. Cetacean Res. Manage., 2020)
The North Pacific right whale (Eubalaena japonica) is among the most endangered of all great whales, having been subject to intensive commercial whaling in the 19th century. All available 20th century records of this species in the North Pacific were reviewed. There has been a total of 1,965 recorded sightings since 1900; of these, 988 came from the western North Pacific, 693 from the eastern North Pacific and 284 had no location specified. Thirteen strandings (all but one from the western North Pacific) were recorded. Known catches for commercial or scientific purposes totalled 742 (331 in the western North Pacific, 411 in the eastern North Pacific). Most of the reported Soviet ‘sightings’ in the eastern North Pacific were actually catches, as may be the case for Soviet sightings in the Okhotsk Sea. In addition, the impact of known Soviet illegal catches in the Okhotsk Sea may be reflected in an apparent decline in sightings after the 1960s (although this may be partly explained by low observer effort). Overall, the data support the hypothesis that at least two stocks of right whales exist in the North Pacific. Any recovery in the western North Pacific population was compromised by the Soviet catches in the Okhotsk region, although recent sightings suggest that this population is still large enough to sustain reproduction. By contrast, Soviet catches in the now-smaller eastern North Pacific population have severely reduced its prospects for recovery. Although the prognosis for this population is poor, a long-term monitoring programme is required to better understand its conservation status and to determine whether it may be affected by human-related problems that would require mitigation.